Kemampuan Komisaris Independen dan Kepemilikan Institusional dalam Memoderasi Pengaruh Manajemen Laba Terhadap Nilai Perusahaan - Viony Sinatraz; Sugi Suhartono (ITB AAS INDONESIA, 2021)
The aim of every company is to earn profit and increase the firm value. When the firm values optimal, the prosperity of its shareholders also increase. Financial statements are one of communicatin media to its users regarding the firm performances. In an effort to enhance the firm value, management tends to deliberately perform certain accounting method, called Earnings Management. Earnings management is done so that the company’s financial statement looks good and healthy in a certain period, although it will cause a decrease in the firm value in the future. One way that can be used to reduce earnings management is to implement good corporate governance. This study aims to determine the effect of earnings management in company value which is moderated by independent commissioners and institusional ownership. The object of this study consist of 90 manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016 – 2018. The sampling techinques was done by purposive sampling. The data analysis method to be used are descriptive statistical analysis, simple regression analysis, moderated regression analysis, classical assumption tests, and goodness of fit test. The results of this study indicate that earnings management is proven to have a negative effect on the firm value, independent commissioners are proven to weaken the effect of earnings management on the firm value, and institutional ownership are proven to weaken the effect of earnings management on the firm value.